Pecuniary knowledge externalities and innovation: Intersectoral linkages and their effects beyond technological spillovers - Agnieszka Gehringer (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2010)
The aim of the paper is to discuss and to provide evidence for the existence of pecuniary knowledge externalities, considered here as the main cause of positive disequilibrium experience by downstream producers. This last effect, confirmed by the empirical analysis here performed, contrasts the postulates of the model of growth through creative destruction due to Aghion & Howitt (1992), where downstream producers remain very much passive in front of new technological knowledge externally generated.
Keywords: 330; pecuniary knowledge externalities; endogenous growth; creative destruction; Input-Output; Wissenstransfer; Lieferanten-Kunden-Beziehung; Branche; Innovation; Panel; Schätzung; Europa